Regional Economic Outlook, April 2016, Western Hemisphere Department : Managing Transitions and Risks - Faruqee, Hamid (Regional Economic Outlook, 2016)
The United States has seen an improvement in economic activity, driven by consumption, and has taken a first step toward gradual normalization of interest rates. The U.S. recovery continues to support activity in Mexico, Central America, and the Caribbean, but China's slowdown has reduced the demand for exports from South America. At the same time, the region's commodity exporters have experienced further terms-of-trade shocks as commodity prices continue their decline globally. This report describes the policies and economic reforms needed to address the declining productive capacity in Latin America and the Caribbean. Three chapters assess corporate vulnerabilities in Latin America, analyze the degree of exchange rate pass-through in the region, and evaluate trends in public and private infrastructure investment.